2021
DOI: 10.12688/aasopenres.13196.2
|View full text |Cite
|
Sign up to set email alerts
|

High infectious disease burden as a basis for the observed high frequency of asymptomatic SARS-CoV-2 infections in sub-Saharan Africa

Abstract: Following the coronavirus outbreaks described as severe acute respiratory syndrome (SARS) in 2003 and the Middle East respiratory syndrome (MERS) in 2012, the world has again been challenged by yet another corona virus, named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). SARS-CoV-2 infections were first detected in a Chinese Province in December 2019 and then declared a pandemic by the World Health Organization in March 2020. An infection caused by SARS-CoV-2 may result in asymptomatic, uncompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…COVID-19 transmission in Africa has been marked by relatively fewer infections, mostly asymptomatic, and lower death rate compared to developed countries. A younger population structure and a variety of socio-ecological factors (i.e., warm weather, low population density and mobility and trained immunity by previous high burden infectious diseases), as well as early public health measures taken by governments (i.e., early lockdown sub-Saharan countries) ( 20 ), have been suggested to explain such lower incidence ( 21 ). Surprisingly, the pandemic has been more pronounced in a few countries (e.g., South Africa, Morocco and Tunisia) suggesting country-specific drivers of SARS-CoV-2 spread and morbidity, but this could also be largely explained by a low and unequal testing capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 transmission in Africa has been marked by relatively fewer infections, mostly asymptomatic, and lower death rate compared to developed countries. A younger population structure and a variety of socio-ecological factors (i.e., warm weather, low population density and mobility and trained immunity by previous high burden infectious diseases), as well as early public health measures taken by governments (i.e., early lockdown sub-Saharan countries) ( 20 ), have been suggested to explain such lower incidence ( 21 ). Surprisingly, the pandemic has been more pronounced in a few countries (e.g., South Africa, Morocco and Tunisia) suggesting country-specific drivers of SARS-CoV-2 spread and morbidity, but this could also be largely explained by a low and unequal testing capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also indicated that malaria-induced immunomodulation could be protective against respiratory viruses, reducing pulmonary inflammatory response inflammation ( 47 , 48 ). Alternatively, the higher burden of infectious diseases in sub-Saharan Africa has been suggested to mediate the asymptomatic SARS-CoV-2 infections by induction of immunological tolerance or trained immunity to other infections such as tuberculosis, other human coronaviruses and even Bacillus Calmette-Guérin (BCG) vaccination ( 21 , 46 ). In addition, other studies have reported that bacterial, fungal and viral co-infections with SARS-CoV-2 are also uncommon, however when present, they may cause a worse outcome ( 49 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aside these pathology-associated immune responses, specific adaptive responses to viral antigens have been demonstrated, although the extent of protection attributable to these responses remains to be fully established. Aside from immunity, other factors such as age, gender and comorbidities [ 116 ], race [ 117 ], socioeconomic status [ 118 ], and infectious disease burden [ 119 ] have variously been identified as important factors that predispose infected persons to either severe, fatal disease, or asymptomatic/mild disease. The cell-mediated immune response is the principal and effective immune response against viral infection.…”
Section: Covid-19 Seroepidemiology In Africa and The Effect Of Co-inf...mentioning
confidence: 99%
“…Spending time outdoors with skin exposure to sunlight also enhances their vitamin D production which is known to boost host immunity [ 120 , 121 ], which may possibly reduce the rate of successful infection and severe disease with COVID-19 [ 122 , 123 ]—as has been indicated more definitively for influenza and other respiratory viruses [ 124 , 125 ]. Others have hypothesized that the chronic exposure of the African population to many pathogens could have induced some tolerance to inflammation; together with the widespread use of live attenuated vaccines, like the Bacillus Calmette-Guérin (BCG) vaccine, which may elicit a bystander protective effect [ 126 ].…”
Section: Aims and Objectivesmentioning
confidence: 99%